2009
DOI: 10.1021/es8037142
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Waste Activated Sludge Protein Conversion and Volatile Fatty Acids Accumulation during Waste Activated Sludge Anaerobic Fermentation by Carbohydrate Substrate Addition: The Effect of pH

Abstract: Volatile fatty acids (VFAs), the carbon source of biological nutrients removal, can be produced by waste activated sludge (WAS) anaerobic fermentation. However, because of high protein content and low carbon to nitrogen mass ratio (C/N) of WAS, the production of VFAs, especially propionic acid, a more preferred VFA than acetic acid for enhanced biological phosphorus removal (EBPR), is limited. After the addition of carbohydrate (rice was used as the model matter) to the WAS anaerobic fermentation system to bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
125
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 410 publications
(147 citation statements)
references
References 31 publications
12
125
5
Order By: Relevance
“…However the difference is not as significant, because for both sets, the results were still much lower than the minimum required C/N ratio of 20:1 (or ideally of 30:1) to be considered as an effective external carbon sources. [3] Note that the C/N ratio or rbCOD/NH 4 + is the most important independent variables in this experiment. Because the fermented biosolids would be added back to the anoxic zone as external carbon source, hence a lower C/N ratio would means: with the same amount of added carbon, more nitrogen would be introduced back into the system.…”
Section: Biosolids Fermentation and Ammonia Strippingmentioning
confidence: 98%
“…However the difference is not as significant, because for both sets, the results were still much lower than the minimum required C/N ratio of 20:1 (or ideally of 30:1) to be considered as an effective external carbon sources. [3] Note that the C/N ratio or rbCOD/NH 4 + is the most important independent variables in this experiment. Because the fermented biosolids would be added back to the anoxic zone as external carbon source, hence a lower C/N ratio would means: with the same amount of added carbon, more nitrogen would be introduced back into the system.…”
Section: Biosolids Fermentation and Ammonia Strippingmentioning
confidence: 98%
“…The purpose behind mixing different waste streams is the development of a substrate with a balanced carbohydrate: protein ratio, which in turn answers for a balanced C/N ratio. According to various experiments [27,28] it has been found that a higher C/N ratio (around 20/1-30/1) can be beneficial to the microorganisms responsible for acidogenesis. Furthermore, it is believed that the carbohydrate amount can have a synergistic effect with WAS.…”
Section: Available Waste Streams For Vfa Production and Vfa Yieldsmentioning
confidence: 99%
“…The composition of the acid fraction of the liquid product depends on various variables, like the type of waste stream used and the fermentation conditions (pH, fermentation time, etc.) [1,28]. The pH value for example plays an important role in the synthesis of different VFA.…”
Section: Available Waste Streams For Vfa Production and Vfa Yieldsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polyethylene glycol (PEG) [7][8][9][10][11], generally treated with nitroterephthalic acid [1,[12][13][14][15] to deactivate alkaline sites, is most often used as a stationary phase for separation of short-chain fatty acids. Other polar stationary phases were also applied to analyse water samples; for example polybiscyanopropyl (90%) -cyanopropylphenylsiloxane (10%) stationary phase to determine acids extracted from plants [16].…”
mentioning
confidence: 99%